Product TDS & test report & sample of K13 acoustic spray paint (RFA-482_Rev C) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.